Infrequent Portfolio Decisions: A Solution to the Forward Discount Puzzle - Bacchetta, Philippe; van Wincoop, Eric (American Economic Review, 2010)
A major puzzle in international finance is that high interest rate currencies tend to appreciate (forward discount puzzle). Motivated by the fact that only a small fraction of foreign currency holdings is actively managed, we calibrate a two-country model in which agents make infrequent portfolio decisions. We show that the model can account for the forward discount puzzle. It can also account for several related empirical phenomena, including that of “delayed overshooting.” We also show that making infrequent portfolio decisions is optimal as the welfare gain from active currency management is smaller than the corresponding fees. (JEL F31, G11, G15)